2016
DOI: 10.3945/ajcn.115.110361
|View full text |Cite
|
Sign up to set email alerts
|

Development of Standard Reference Materials to support assessment of iodine status for nutritional and public health purposes

Abstract: The use of urinary iodine as an indicator of iodine status relies in part on the accuracy of the analytical measurement of iodine in urine. Likewise, the use of dietary iodine intake as an indicator of iodine status relies in part on the accuracy of the analytical measurement of iodine in dietary sources, including foods and dietary supplements. Similarly, the use of specific serum biomarkers of thyroid function to screen for both iodine deficiency and iodine excess relies in part on the accuracy of the analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In terms of analytical methodology, the ICP-MS method [ 76 ] is suitable for the analysis of iodine in a variety of foods, as well as dietary supplements, and is known to have good precision and accuracy. Using the ICP-MS method, the USDA contract laboratory has shown that it can generate accurate iodine values that compare well with the iodine values of several NIST-certified reference materials (CRM), notably NIST 1849a Infant/Adult Nutritional Formula and 1548a Typical Diet [ 21 , 78 , 80 ]. For quality control during analysis of samples, the USDA is using these CRM reference materials, as well as in-house control materials cross-validated to the NIST materials.…”
Section: Developing An Iodine Database For Us Foods—recent Progresmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of analytical methodology, the ICP-MS method [ 76 ] is suitable for the analysis of iodine in a variety of foods, as well as dietary supplements, and is known to have good precision and accuracy. Using the ICP-MS method, the USDA contract laboratory has shown that it can generate accurate iodine values that compare well with the iodine values of several NIST-certified reference materials (CRM), notably NIST 1849a Infant/Adult Nutritional Formula and 1548a Typical Diet [ 21 , 78 , 80 ]. For quality control during analysis of samples, the USDA is using these CRM reference materials, as well as in-house control materials cross-validated to the NIST materials.…”
Section: Developing An Iodine Database For Us Foods—recent Progresmentioning
confidence: 99%
“…Also, iodine derived from dietary supplements must be included along with foods in order to accurately assess total intake; therefore, data are needed on the iodine content of supplements [ 20 ]. Robust approaches to developing databases will include choosing appropriate analytical methodology (including use of standard reference materials [ 21 , 22 ]); designing and implementing sampling plans with good coverage of major country-specific contributors (from foods, beverages, dietary supplements, and salt); and publishing the results in database formats or tables that allow linkage with population surveys and individual intake records (such as food frequency questionnaires and 24-h recalls).…”
Section: Introductionmentioning
confidence: 99%
“…Either of these human milk CRMs, which would reside in sector 6, could also be analyzed to determine organic nutrients. A reference value for iodine was added recently to SRM 1953 to address this important inorganic nutrient in human milk [98] and to complement the other nutritional elements listed. Yerba mate (SRM 3253), shown in sector 5 of Fig.…”
Section: Future Crm Needs For Organic Nutrientsmentioning
confidence: 99%
“…Standard Reference Materials (SRMs) are CRMs issued by the NIST. The NIST is developing breast-milk SRMs that are valid over a limited range of iodine concentrations, but breast-milk CRMs or SRMs covering a wider range of iodine concentrations will still be needed (35). The NIST is also developing trimester-specific serum CRMs or SRMs that span the full range of results for all serum tests of thyroid function (35).…”
Section: Development Of Reference Materials For Biological Samplesmentioning
confidence: 99%